PERANCANGAN SISTEM INFORMASI E-MARKETPLACE EVENT ONLINE UNTUK MENINGKATKAN PEMASARAN DIGITAL BERBASIS MOBILE - Norma Ningsih; Aprianto; Onastatia Sahartian (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
An event is an activity carried out to celebrate a certain moment, whether it is held in public or private. In recent years, Events have been used as a business object and already have a sizeable market. Online events are expected to continue to be a trend that will develop in the future. However, on the other hand, there are still problems faced by both the organizers and the general public, namely difficulties in disseminating and obtaining information related to an event and coordination of ticket sales that has not been maximized. The purpose of this research is to provide an information system solution for organizing an online event in the form of designing a marketplace information system that can be used as a forum for all events spread across various platforms to be centralized into one platform. The information system design method used is the waterfall method with the concept of gamification to maintain and increase user loyalty. The results of this study are in the form of an information system design that can handle event sales and purchase transactions in which users and event organizers can be connected to each other.